Pengaruh Pemberian Dosis Pupuk Organik Cair Terhadap Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays saccarata Sturt) - Arief Rohman Faruq; Adrianus Adrianus adrianus; Amelia Limbongan (Musamus Journal of Agrotechnology Research, 2022)
This research aims to determine the best dose of Papuagro liquid organic fertilizer on the growthand production of sweet corn (Zea Mays Saccarata Sturt) in Yasa Mulya Village, Tanah Miring,Merauke Regency. This study use a randomized block design experiment, with 5 treatments and3 replications. This research shows that the combination treatment of dosing of Papuagro liquidorganic fertilizer gives the significant influence at the level of 0.05% on cob’s diameter and thetotal weight per plot. While at the level of 0.01% gives a significant influence on the number ofseeds per line, cob’s weights per plant samples. In some of these combination of liquid organicfertilizer dose treatments are able to give a good results. The treatment of Papuagro liquid organicfertilizer dosing using the D3 combination (140ml and 90ml/ 15 L water) gives the best result insome observation than other treatment.Keywords: Sweet Corn; Growth; Production; Organic Liquid Fertilizer Dose.